Data on the utilization of paraneoplastic syndrome autoantibody testing at an academic medical center - Matthew D. Krasowski (Elsevier, 2021)
Paraneoplastic syndromes are rare conditions associated with characteristic autoantibodies produced by malignancy, although similar autoantibodies and clinical presentations may occur in the absence of any neoplasm. Testing for paraneoplastic syndromes often involves panels of autoantibody assays. While autoantibody testing may reveal or confirm actionable clinical diagnoses, inappropriate utilization of testing may be low yield and further lead to false positives that may confuse the clinical picture. There is thus opportunity to improve patient care by analyzing patterns of paraneoplastic autoantibody test utilization. The data in this article provides results from detailed retrospective review of patients tested by 7 autoantibody tests or test panels offered by two large reference laboratories in the United States. The data include 1,446 tests performed on 1,338 unique patients at an academic medical center. For all results, detailed chart review revealed main category of presenting symptoms, patient location at time of testing (either inpatient or outpatient), sex, age, whether cancer was present at the time of testing or later detected, and the specific results of the testing. The data are summarized by category of testing and specific autoantibodies.